Effects of Oil Spills on Marine and Coastal Wildlife - Holly K. Ober (EDIS)
WEC285, a 4-page fact sheet by Holly K. Ober, provides an overview of direct and indirect effects of oil spills on wildlife, factors influencing the degree of impact, susceptibility of various types of wildlife, and the history of oil spills in the Gulf of Mexico. Includes sources of additional information. Published by the UF Department of Wildlife Ecology and Conservation, May 2010.